A study of International Issues through cartoon communication: the cases of Pakistan and Norwegian newspapers from september 2008 to February 2009 - Ayesha Ashfaq, (Universiti Kebangsaan Malaysian, 2012)
This paper is a study of relationship of print media cartoons and the portrayal of international issues. This is an effort to explore the portrayal of international issues through the cartoons published in the two Norwegian newspapers (the VG & the Aftenposten) and the two Pakistani newspapers (The News & the Nation) from September 2008 to February 2009.For the sake of evaluating the nature, degree, frequency and stance of the international cartoons, the international issues, variables and categories are constructed under the light of main postulates of the one aspect of the Agenda Setting Theory that is “Framing”. Through a content analysis (both qualitative and quantitative), Discourse analysis and interview method, it identifies that in the case of the Norwegian newspapers, the VG is more critical than the Aftenposten, while in the case of Pakistani newspapers, the Nation is more critical than The News regarding the cartoon coverage of international issues during this selected period. The international issues were not covered and criticized equally by both cases as there may be some hidden pressure to the cartoonists to suggest what to sketch or not? How to portray or not?